2016
DOI: 10.1123/pes.2015-0283
|View full text |Cite
|
Sign up to set email alerts
|

The 1,500-m Rowing Performance is Highly Dependent on Modified Wingate Anaerobic Test Performance in National-Level Adolescent Rowers

Abstract: Our results highlight the importance of considering the contribution of total muscle mass and anaerobic energy pathways to 1,500-m rowing performance in competitive adolescent rowers. Therefore, the modified Wingate test could be used by rowing coaches to potentially identify talented young rowers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
2
21
0
6
Order By: Relevance
“…A cycle-based WAnT only assesses lower-body anaerobic power, while rowing involves full-body mechanics. Previous studies have shown that the modified WAnT on a Concept II rowing displayed strong correlations with rowing performance [ 5 , 6 , 37 ] and produced significantly higher peak power outputs than cycle testing [ 31 ]. Conversely, Cerasola et al [ 38 ] found a near-perfect association between 2K performance and cycle WAnT peak power ( r = 0.90) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cycle-based WAnT only assesses lower-body anaerobic power, while rowing involves full-body mechanics. Previous studies have shown that the modified WAnT on a Concept II rowing displayed strong correlations with rowing performance [ 5 , 6 , 37 ] and produced significantly higher peak power outputs than cycle testing [ 31 ]. Conversely, Cerasola et al [ 38 ] found a near-perfect association between 2K performance and cycle WAnT peak power ( r = 0.90) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic power is also important, specifically during the start and final “leg” of a race [ 5 ]. The Wingate anaerobic test (WAnT) is arguably the most widely used test of anaerobic fitness, and has been established as a valid measure of anaerobic power output during maximal short-term cycling and arm cranking exercise [ 6 ]. Unfortunately, traditional 2max and WAnT tests are performed in laboratory settings requiring long durations, expensive equipment, and knowledgeable technicians, which may be too impractical for coaches overseeing large teams with time and budget limitations, commonly seen at the collegiate level.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the difference between the 500 and the 1,000-m test is large, 700-m ergo tests are always performed at the beginning of the age category 13 to familiarize young rowers with the longer test distances. High test retest reliability and correlations for different distances on rowing ergometer were approved in different studies ( Ingham et al, 2002 ; Soper and Hume, 2004 ; Maciejewski et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…6 Some results on the rowing ergometer can be considered as important predictors of the boat performance on the water. 9.12-14 Certain research attempts to predict rowing performance through anthropometric variables, 15,16 upper limb power 11 lower limb strenght 17 and tests on the rowing ergometer 1,6,18 . Therefore, the Brazilian Rowing Confederation adopts the National Rower Evaluation System (SNAR), for athletes interested in competing in the Brazilian Rowing Championship (CBR) and the National Selective Championship, in its different categories, also serving as a complementary assessment for joining the Brazilian Rowing Team.…”
Section: Introductionmentioning
confidence: 99%